2019
DOI: 10.1371/journal.pone.0215117
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and awareness of cervical cancer in Southwestern Ethiopia is lacking: A descriptive analysis

Abstract: PurposeCervical cancer remains the second most common cancer and cancer-related death among women in Ethiopia. This is the first study, to our knowledge, describing the demographic, and clinicopathologic characteristics of cervical cancer cases in a mainly rural, Southwestern Ethiopian population with a low literacy rate to provide data on the cervical cancer burden and help guide future prevention and intervention efforts.MethodsA descriptive analysis of 154 cervical cancer cases at the Jimma University Teach… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
4
10
0
1
Order By: Relevance
“…Two articles [22,23] from Addis Ababa and one article [24] was from Sidama regional state. The number of participants in each included article varied from 154 [25] to 1186 [26]. Overall, this review contains reports of 14,549 study participants.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two articles [22,23] from Addis Ababa and one article [24] was from Sidama regional state. The number of participants in each included article varied from 154 [25] to 1186 [26]. Overall, this review contains reports of 14,549 study participants.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…With regard to the HIV status of the study participants, two of the included studies employed all HIV-positive women [27,28]. The other three studies, [24][25][26] reported the proportion of HIV positive women at 5.5%. 8.7 and 22%, respectively.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…10,11 Different studies also revealed that knowledge of women about cervical cancer is very low in Ethiopia. [12][13][14][15][16] The majority of respondents in previous studies have heard about cervical cancer, but not more than half of respondents know what causes cervical cancer and the risk factors associated with the disease. 17,18 Women's age, marital status, occupation, educational status, source of information, knowing someone with cervical cancer and health-seeking behavior were found to be associated with cervical cancer knowledge in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research in Ethiopia demonstrated that whilst knowledge and education were low, majority had never attended school neither ever heard of cervical cancer before. 7 The results of analysis on the relationship between several variables showed a significantly increased risk of cervical cancer with a p value under 0.05 (as shown in Table 2). Among those variables were: age at menarche, age at first sexual intercourse, number of sexual partners and parity.…”
Section: Methodsmentioning
confidence: 94%
“…4,5 In poor and developing countries, cervical cancer dominates as the cause of death in women, for example cervical cancer is the second most common cancer and cause of death in Ethiopia. 6,7 In developing countries, cervical cancer ranks seventh as the most commoncancer and accounts up to 3.2% of mortality due to cancer. 8,9 In Indonesia, cervical cancer is the most common cancer in women after breast cancer.…”
Section: Introductionmentioning
confidence: 99%